Different electromyographic features of the gastrocnemius and the tibialis anterior muscles when comparing three types of service among young sportsmen and sportswomen - Mourtzios, C.; Arvanitidou, V.; Athanailidis, I.; Kostopoulos, N. (Journal of Human Sport & Exercise, 2021)
This study examines the electromyographic activity of lower extremities and, in particular, of the tibialis anterior among young tennis players aged 12-16 years when performing three types of service, namely flat, slice and topspin. The study sample included 9 athletes. In order to record the muscle electric activity, three active surface electrodes were used with a pre-amplifier (Motion Control Co). Fluctuation analysis did not show statistically significant differences between parameters. Differences were observed in the activation sequence between the two muscles. In the flat service, the gastrocnemius is the first one activated, followed by the tibialis anterior. Maximum activation of the gastrocnemius occurs at initial lift-off, while the tibialis anterior towards the end of lift-off. In slice service, the two muscles are activated together and their maximum activation occurs when lift-off starts. In topspin service, the gastrocnemius is the first one activated, followed by the tibialis anterior. Maximum activation of the gastrocnemius occurs at initial lift-off, while the tibialis anterior towards the end of lift-off. Maximum activation of the two muscles occurred at the start of lift-off in all three service modes. In conclusion, young athletes need training to strengthen the tibialis anterior so as to improve lift-off velocity/acceleration in the service motion. Additionally, strengthening the tibialis anterior is a tool to improve foot lead. Such techniques are of the utmost importance during training so that skills as elaborate as those required for tennis service may be developed among young players.